Research status of bael (Aegle marmelos) in India: A review - SINGH, A K; SINGH, SANJAY; SAROJ, P L; KRISHNA, HARE; SINGH, R S; SINGH, R K (The Indian Journal of Agricultural Sciences, 2019)
Bael [Aegle marmelos (L.) Correa ex Roxb., Family Rutaceae] is one of the oldest known fruit tree species native to India. Wide distribution of bael in Indian subcontinent and other parts of the world reflects its adaptation to a range of agro-climatic conditions. In addition to well-known nutritional and traditional medicinal benefits, the bael fruits have considerable processing and industrial values. In order to better utilize and improve the existing genetic resource, there is a need scrutinizing the studies related to genetic diversity, characterization, evaluation and conservation, taxonomy, phenology, floral biology and pollination. In addition, survey of literature for better understanding of various agrotechniques, propagation methods, canopy management, biotic and abiotic stresses and their management is equally important for improving the fruit productivity and quality.Accordingly, this review paper intends to critically examine and systematically arrange the voluminous literature available on aforementioned aspects of bael tree.